A Descriptive Study of Thesis Completion Challenges Among Medical Students - Neneng Suryadinata; Gladies Mercya Neolaka; Rohana Uly Pradita Siregar (Fakultas Kedokteran Universitas Pelita Harapan, 2025)
Background: The Final Project (FP) is a mandatory course for medical education students, typically undertaken in the sixth semester. It is divided into two stages: Final Project 1 (FP1) and Final Project 2 (FP2). In FP1, students develop, document, and present a research proposal, while in FP2, they execute the planned research, analyze the results, and present their findings. A decline in FP2 completion rates was observed in 2024, raising concerns about factors affecting student performance. Methods: A descriptive analysis methods approach was used, combining quantitative surveys (n=91) and qualitative interviews. The survey, with 10 questions on a 4-point Likert scale, assessed factors affecting FP2 completion. Semi-structured interviews and written responses explored deeper insights, with thematic analysis identifying key barriers. Results: Survey results revealed moderate motivation (mean=2.77) and high procrastination (mean=3.01). Time management (mean=2.86) and personal issues (mean=2.35) were significant challenges. The main delays were lack of motivation (36.26%) and time management issues (27.47%). Themes from interviews included motivation, time management, supervisor support, data access, and mental health. Conclusions: Students face key challenges in completing the FP2 course, particularly low motivation, poor time management, and limited supervisor interaction. Addressing these issues through enhanced intrinsic motivation, effective feedback, and structured time management can foster more successful and high-effort student profiles.